Tourist Comfort And Safety Study Case Study: Ogan Komering Ilir District - Dirgantara, Ahmad Rimba; Zallesa, Sheila; Baswarani, Delfta Tunjung (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
The tourism development in South Sumatra Province, particularly in Ogan Komering Regency, has excellent potential. Ogan Komering Ilir Regency is a supporting district of Palembang City, with its main attractions being natural, cultural, and creative economy tourism. However, the growth of the tourism industry is separate from physical and non-physical infrastructure development. The physical infrastructure is seen in the inadequate access to tourist destinations. In contrast, the non-physical infrastructure still faces high crime levels due to the lack of physical infrastructure such as street lighting and electricity. This research aims to identify the factors that affect the comfort and safety of tourists visiting Ogan Komering Ilir Regency and to evaluate the efforts made by related stakeholders in addressing these issues. The methodology used in this research is a mixed methodology with descriptive analysis through relevant literature sources. The results of this research show that the level of comfort and safety is the top priority for tourists when visiting a destination. The role of related stakeholders in making and implementing policies is essential.